Common planning time in middle level schools : research studies from the MLER SIG's national project - Mertens, Steven B.; Mertens, Steven B. (Handbook of research in middle level education series., 2013)
This volume, the ninth volume in the Handbook of Research in Middle Level Education, is a compilation of research studies focusing on the use and implementation of common planning time (CPT) in middle level schools. All of the studies were part of the Middle Level Education Research SIG's National Middle Grades Research Project (NMGRP) on Common Planning Time, which provides additional evidence about teachers' understandings, experiences, the benefits and barriers about CPT.Since all researchers participating in the SIG-sponsored project utilized the same data collection protocols and followed the same protocols, the overall data collection was systematic and is highly reliable. Five research questions were generated to guide the development of the data collection protocols. While the authors were encouraged to use their data to address these project-level questions, they were not required to do so. The project consisted of both qualitative and quantitative data collection. Phase I (qualitative) consisted of observations of CPT meetings and structured interviews with teachers. Phase II (quantitative) was comprised of an online teacher survey. Within the chapters of this volume, a variety of relevant and meaningful research questions are examined utilizing both qualitative and quantitative methodologies.